Association between use of liraglutide and liver fibrosis in patients with type 2 diabetes - Tan, Yijiong; Zhen, Qin; Ding, Xiaoying; Shen, Tingting; Liu, Fang; Wang, Yufan; Zhang, Qidi; Lin, Renkun; Chen, Lili; Peng, Yongde; Fan, Nengguang (Frontiers in Endocrinology, 2022)
Objective: Patients with type 2 diabetes have a high risk of non-alcoholic fatty liver disease (NAFLD) and related liver fibrosis. Glucagon-like peptide-1 receptor agonists (GLP-1RAs) have demonstrated efficacy in improving NAFLD, while their effectiveness on liver fibrosis is limited in type 2 diabetic patients. Materials/Methods: A prospective cohort study was performed in type 2 diabetic patients. The study subjects were divided into two groups based on the use of liraglutide or not, and propensity score matching (PSM) was also conducted. After 12 months follow-up, liver fibrosis was assessed by NAFLD fibrosis score (NFS) fibrosis-4 (FIB-4),and liver stiffness measurement (LSM). The association between liraglutide use and liver fibrosis was analyzed by multivariable linear regression. Results: In the current study, a total of 1765 type 2 diabetic patients were enrolled. 262 patients were liraglutide user and 1503 were nouser.. After 12 months follow-up, liraglutide use tended to be associated with reduced prevalence of advanced fibrosis (3.1% vs. 6.1%, P = 0.218). After adjustment for confounding factors, multivariable linear regression revealed that liraglutide use was negatively associated with decreased NFS (β= -0.34，P = 0.043), FIB4 (β= -0.26，P = 0.044) and LSM (β= -4.95，P = 0.007) in type 2 diabetics. The results after PSM were similar to those before PSM. Conclusions: Liraglutide treatment is associated with decreased liver fibrosis in type 2 diabetic subjects.